2015
DOI: 10.1111/ped.12816
|View full text |Cite
|
Sign up to set email alerts
|

Regression of massive cardiac rhabdomyoma on everolimus therapy

Abstract: Cardiac rhabdomyoma is the primary feature of the genetic disease, tuberous sclerosis complex, the most common cardiac tumor diagnosed in neonates and infants. Spontaneous regression is observed in most cases, but these tumors may cause hemodynamic instability, arrhythmias or other complications. We describe the case of a critically ill neonate, resuscitated after cardiac arrest secondary to massive locally invasive cardiac rhabdomyoma, who was successfully treated with everolimus (mammalian target of rapamyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 10 publications
1
27
0
2
Order By: Relevance
“…10 To date, several cases of cardiac rhabdomyomas treated successfully with everolimus have been described (Table 1). 1,2,4,6,7,9,[11][12][13][14][15][16][17][18][19][20][21] However, the United States Food and Drug Administration has not approved the treatment of cardiac rhabdomyomas with mammalian target of rapamycin inhibitors. 1 We report a case of a giant rhabdomyoma of the left ventricle, causing severe left ventricular dysfunction and leading to a ductdependent systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 To date, several cases of cardiac rhabdomyomas treated successfully with everolimus have been described (Table 1). 1,2,4,6,7,9,[11][12][13][14][15][16][17][18][19][20][21] However, the United States Food and Drug Administration has not approved the treatment of cardiac rhabdomyomas with mammalian target of rapamycin inhibitors. 1 We report a case of a giant rhabdomyoma of the left ventricle, causing severe left ventricular dysfunction and leading to a ductdependent systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Successful pregnancies in women undergoing everolimus treatment have been reported without teratogenic manifestations in the neonate. 1 However, hyperglycaemia and hyperlipidaemia could be fetal risk factors that should be considered. 1 This is the largest cardiac rhabdomyoma of the left ventricle reported, presenting with an accelerated response to everolimus and no significant adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection can be considered for severe cases 34 . Several case reports have also described the successful treatment of rhabdomyomas with everolimus, the mTOR complex 1 inhibitor 35,36 . Everolimus treatment was associated with rapid tumour regression, as observed on echocardiography.…”
Section: Rhabdomyomamentioning
confidence: 96%
“…Bader et al 19 reported 18 live births with prenatally diagnosed rhabdomyomas, seven of whom had cardiac symptoms, with medical treatment being required in four cases and surgical intervention in three cases. In addition, everolimus (a mammalian target of rapamycin inhibitor), 20,21 an agent approved for the treatment of organ rejection in renal transplantation, various renal and neuroendocrine tumors, and tuberous sclerosis-associated subependymal giant cell astrocytomas, has succeeded in treating massive or multifocal cardiac rhabdomyomas. With an optimal dose of the drug (0.5 mg daily, 2 days per week), remarkable tumor regression was achieved at 10 months of age.…”
Section: Rhabdomyomamentioning
confidence: 99%
“…With an optimal dose of the drug (0.5 mg daily, 2 days per week), remarkable tumor regression was achieved at 10 months of age. 20 Nowadays, everolimus is used for the treatment of inoperable multifocal cardiac rhabdomyomas. 21…”
Section: Rhabdomyomamentioning
confidence: 99%